2000
DOI: 10.1093/oxfordjournals.jmicro.a023859
|View full text |Cite
|
Sign up to set email alerts
|

An ultrastructural study on the effect of streptozotocin on the islets of Langerhans in mice

Abstract: The ultrastructural changes in the morphology of the islets of Langerhans in response to streptozotocin were studied in the mice pancreas. Male white albino CSI mice were given a single intravenous injection of 75 mg kg(-1) body weight streptozotocin, and were sacrificed at different time intervals up to 48 h following the treatment. Their pancreases were excised and randomly processed for electron microscopic examination. Hyperglycaemia and glucosuria were detected 8 h after treatment, became remarkably high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
10
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 0 publications
6
10
0
Order By: Relevance
“…In this study, in the group of STZinduced diabetes mitochondrial vacuolization and swelling, as well as dilatation of the endoplasmic reticulum and decrease in the secretory granules were seen in the b-cell of Langerhans islets. Our results were similar to other studies, a decrease in the secretory granules, nuclear shrinkage and pycnosis, swelling of mitochondria and endoplasmic reticulum, round-shaped mitochondria, hypertrophied cytoplasmic organelles such as Golgi and endoplasmic reticulum in the STZ-induced diabetic rat b-cells were shown by electron microscopy (Papaccio et al 1991;Aughsteen 2000;Bolkent et al 2000;Hong et al 2002).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, in the group of STZinduced diabetes mitochondrial vacuolization and swelling, as well as dilatation of the endoplasmic reticulum and decrease in the secretory granules were seen in the b-cell of Langerhans islets. Our results were similar to other studies, a decrease in the secretory granules, nuclear shrinkage and pycnosis, swelling of mitochondria and endoplasmic reticulum, round-shaped mitochondria, hypertrophied cytoplasmic organelles such as Golgi and endoplasmic reticulum in the STZ-induced diabetic rat b-cells were shown by electron microscopy (Papaccio et al 1991;Aughsteen 2000;Bolkent et al 2000;Hong et al 2002).…”
Section: Discussionsupporting
confidence: 92%
“…In STZ-induced diabetes, specific toxicty of STZ on pancreatic b-cells has been studied for many years in various experimental studies (Das et al 1996;Aughsteen 2000;Hong et al 2002). In addition to, some plants have been used for diabetes treatments in recent years (Hess et al 1986;Das et al 1996;Bolkent et al 2000;Degirmenci et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…First, this pathway is the major pathway involved in apoptosis mediated by serum deprivation (39). Second, the Bcl gene family is also involved in other pathways of cell death, including necrosis (41), which may be the pathway of cell death mediated by STZ (42). Third, inhibition of apoptosis by PTHrP in breast cancer cells and chondrocytes is thought to be mediated through upregulation of Bcl-2 mRNA and protein (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…After screening of pancreata of murine diabetes animal models by morphologic analysis via light microscopy or by methods to detect DNA strand breaks on tissue sections, islet cell apoptosis has been suggested to occur in these animals (Augstein et al, 1998;Cardinal et al, 2001;George et al, 2002;Hill et al, 1999;Kurrer et al, 1997;Lally et al, 2001;O'Brien et al, 1996O'Brien et al, , 1997. In contrast, in mice treated with low-dose Sz, analysis by electron microscopy showed necrosis to be the dominant or even sole mode of islet cell death (Aughsteen, 2000;Kolb-Bachofen et al, 1988;Like et al, 1978;Papaccio et al, 1991), and apoptosis was found only in infiltrating lymphocytes (SainioPöllänen et al, 1998). It is thus unclear whether islet cell death during IDDM development occurs by necrosis, by apoptosis, or by a combination of both Mauricio and Mandrup-Poulsen, 1998;Pipeleers et al, 2001 Because the type of cell death may define the strategy to prevent IDDM, we investigated the mode of islet cell death in prediabetic diabetes-prone (dp) BB rats.…”
mentioning
confidence: 99%